1989
DOI: 10.1002/aic.690350714
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature adsorption of alkali vapors on solid sorbents

Abstract: Vapors of alkali metal compounds can be removed from coal combustion and gasification flue gases using high-temperature aluminosilicate sorbents. The fundamentals of alkali adsorption on kaolinite, bauxite, and emathlite are compared and analyzed both experimentally and through theoretical modeling. The results show that the process is not a simple physical condensation, but a complex combination of diffusion and reaction. The kinetics of adsorption on these sorbents have similarities: the process is diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 9 publications
4
91
1
Order By: Relevance
“…25,64,66,[138][139][140][141][142][143][144][145][146][147][148][149] Shadman and et al 139,[150][151][152] have demonstrated the effectiveness of sorbents (alumina, bauxite, emathlite, kaolinite, silica, limestone) for the capture of lead, cadmium, and other alkali metal vapors. Wu et al 181 extended their earlier studies to the development of a multifunctional sorbent for capture of sulfur dioxide, alkali metals, and lead.…”
Section: Sorbent Methodologiesmentioning
confidence: 99%
“…25,64,66,[138][139][140][141][142][143][144][145][146][147][148][149] Shadman and et al 139,[150][151][152] have demonstrated the effectiveness of sorbents (alumina, bauxite, emathlite, kaolinite, silica, limestone) for the capture of lead, cadmium, and other alkali metal vapors. Wu et al 181 extended their earlier studies to the development of a multifunctional sorbent for capture of sulfur dioxide, alkali metals, and lead.…”
Section: Sorbent Methodologiesmentioning
confidence: 99%
“…An ideal getter material would possess characteristics of high temperature compatibility, rapid rates of adsorption, high loading capacity, transformation of alkali into a less corrosive form, and irreversible adsorption to prevent the release of adsorbed alkali during process fluctuations. Much of the past getter research [14][15][16][17][18][19][20][21][22] was concerned primarily with cleaning hightemperature (~800°-900°C) flue gases from pressurized, fluidized-bed combustors (PFBC) for use in gas turbine power generation applications. Getter beds were to be employed to simultaneously remove particulate and vapor-phase alkali.…”
mentioning
confidence: 99%
“…At higher temperatures, alkali chlorides may react with the silica or alumina phases in the plant skeleton or in the external soil. SEM-EDX and thermodynamic modeling have shown how especially aluminosilicates are highly reactive toward the incorporation of alkali metals: 16,21,28,29,41 2NaClðg, lÞ þ H 2 OðgÞ þ xYðsÞ T Na 2 O 3 xYðs, lÞ þ 2HClðgÞ ð2Þ where Y(s) signifies either a pure silica phase, 19 a pure alumina phase, 19 or combinations hereof. 19,20 At moderate temperatures, reaction 2 is kinetically limited, 19,20 and the competition from alkali chloride evaporation at temperatures exceeding 700°C is significant.…”
Section: ' Introductionmentioning
confidence: 99%